Análise das habilidades visuoconstrutivas em idosos cognitivamente saudáveis e com comprometimento cognitivo leve dos tipos amnésico e não amnésico - Malagueta, Geórgia Luana Leitão (2022)
Mild Cognitive Impairment (MCI) is characterized by impairments in cognition, above what is expected for age, but not severe enough to cause significant functional deficits. MCI has been widely studied because, compared to healthy elderly people, patients with this condition have a higher risk of progressing to a dementia syndrome. Among the different classifications of MCI, it is possible to highlight those in which there is mnemonic impairment, called amnesic MCI (MCIa), or even those that do not present deficits in this cognitive domain, called non-amnesic MCI (MCIna). Deficits in visuoconstructive skills are important for the identification of neurocognitive disorders, despite this, the neuropsychological measures used are usually limited to less complex and generalist tasks. The objective of this study was to analyze the performance of cognitively healthy elderly people with MCIa and MCIna in two-dimensional visual-constructive graphomotor tasks and in non-graphomotor, two-dimensional, three-dimensional and mental tasks, in the modalities of copying and verbal command. A total of 48 elderly people participated in the study, of which 27 presented healthy cognitive aging, 10 MCIa and 11 MCIna. The results showed that, when differences between groups were found through the use of visuoconstructive measures, participants with MCI showed lower performance than the control group. In addition, only the mental construction tasks and the three-dimensional task in the verbal command modality were able to differentiate both MCI groups from the control group. In the comparisons between the MCIa and MCIna groups, it was observed that, although there was no statistical difference, moderate effect sizes were found in the comparisons using two-dimensional (FCR-copy and WAIS-III Cubes) and three-dimensional (Jigsaw Puzzles imagery). The findings indicate that the visuoconstructive capacity may already be impaired in the initial stages of cognitive impairment, in addition, different modalities of measures should be used, as the performance of the participants tends to vary depending on the visuoconstructive task analyzed. Thus, it is important to seek to understand how the visuoconstructive capacity behaves in cognitively healthy elderly people, as well as in those with cognitive impairments, paying attention to the development of longitudinal studies that can seek to understand how visuoconstructive changes occur, in view of the initial manifestations of each pathological etiology.